PRINCIPLES OF LEXICAL MINIMUM SELECTION FOR TEACHING GENERAL TECHNICAL ENGLISH TO ENGINEERING STUDENTS - O. L. Yaroshenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2014)
The article covers problems related to selecting lexical material for teaching engineers-to-be and surveys the history of the problem. It contains the definition of the "lexical minimum" as a term, and analyses principles of selecting the lexical minimum based both on topics covered by English for Technical Purposes program and requirements for the B2+ level which is the target level of studying English during the first two years on technical faculties. The article explains the importance of selecting the lexical minimum as it makes up the base for exercises used to form lexical competence in reading, speaking, listening, writing and translating. The absence of the lexical minimum makes it much more difficult for a teacher to control and evaluate the formation of the foreign language competence. Taking into account that selection of lexical minimum must be carried out with consideration of many factors (such as program requirements, learning environment and language skills) and certain principles and procedures, it is necessary to draw up an algorithm of actions to select lexical units. The article has four parts: an introduction explaining the topicality, aims and objectives of the article, two parts with the main research material and conclusions.